2018
DOI: 10.1128/msphere.00579-17
|View full text |Cite
|
Sign up to set email alerts
|

The Small RNA ncS35 Regulates Growth in Burkholderia cenocepacia J2315

Abstract: Small RNAs play an important role in the survival of bacteria in diverse environments. We explored the physiological role of ncS35, a small RNA expressed in B. cenocepacia J2315, an opportunistic pathogen in cystic fibrosis patients. In cystic fibrosis patients, infections can lead to “cepacia syndrome,” a rapidly progressing and often fatal pneumonia. Infections with Burkholderia spp. are difficult to threat with antibiotics because of their high intrinsic resistance and ability to form biofilms. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…katB and BCAM0931 are predicted as targets for BrrF. katA did not change expression upon iron depletion (Table S2) and BCAS0635 is not expressed under iron-replete conditions [22]. Taken together, this suggest the increased sensitivity to H 2 O 2 can be linked to downregulation of katB .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…katB and BCAM0931 are predicted as targets for BrrF. katA did not change expression upon iron depletion (Table S2) and BCAS0635 is not expressed under iron-replete conditions [22]. Taken together, this suggest the increased sensitivity to H 2 O 2 can be linked to downregulation of katB .…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that sRNA BrrF is involved in downregulating TCA and oxidative stress response in B. cenocepacia J2315. This sRNA can be added to the growing list of sRNA involved in regulating metabolism, growth and stress responses in the versatile opportunistic pathogen B. cenocepacia [22, 26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…qPCR was performed in a CFX96 Real-Time System C1000 Thermal Cycler (Bio-Rad, Hercules, CA, USA) using GoTaq qPCR Master Mix (Promega, Madison, WI, USA). Cq values were normalised against a previously-validated control gene ( rpo D, BCAM0918) (51, 52). Fold changes were calculated compared to a standard (mix of all cDNAs in experiment) and log-transformed.…”
Section: Methodsmentioning
confidence: 99%
“…Originally, CopraRNA was successfully tested on 18 well-known Enterobacteriaceae sRNAs and on a small number of sRNAs from different bacteria revealing the previously identified mRNA targets as well as novel base pairing interactions (Wright et al, 2013). In the following, multiple studies confirmed the power of such approach in diverse bacterial groups including, for example, Cyanobacteria (Synechocystis: PsrR1 , NsiR4 (Klähn et al, 2015), IsaR1 (Georg et al, 2017); Anabaena: NsrR1 (Álvarez-Escribano, Vioque, & Muro-Pastor, 2018, p. 1)), Firmicutes (Bacillus: RsaE (Durand et al, 2015)), γ-Proteobacteria (Pseudomonas: RgsA (Lu et al, 2016)), α-Proteobacteria (Agrobacterium: AbcR1 (Overlöper et al, 2014); Sinorhizobium: EcpR1, GspR (Robledo et al, 2018)), or β-Proteobacteria (Burkholderia: ncS35, Neisseria: FnrS (Kiekens, Sass, Van Nieuwerburgh, Deforce, & Coenye, 2018;Wright et al, 2013)).…”
Section: Advan Ced Algorithmic Approache S In the Identifi C Ati Onmentioning
confidence: 99%